Pengaruh Kadar Resin Terhadap Sifat Fisik dan Kekuatan Tekan Inti Komposit Sandwich Tenunan 3D Serat Gelas – Poliester - Hermawan Judawisastra; Handy Budiman; Dodi Ihsan Taufiq (Jurnal Metalurgi dan Material Indonesia, 2019)
Sandwich composite is made of light and thick core in between two thin skins that has high mechanical properties. This material is famous for application that needs high specific bending strength for example in lightweight panel for wall or floor for lightweight vehicles. Sandwich composite which made by using woven 3D fiber fabric has the highest resistance delamination resistance among other sandwich material. But, core compression strength of this type of sandwich composite is lower compared to honeycomb or balsa sandwich. Composite polymer properties are determined by resin content. In this research, the effect of resin content to compressive strength and physical properties of sandwich composite 3D woven fabric glass fiber – polyester is studied. Sandwich composite is made by hand lay-up method with resin content variation. Physical properties that are evaluated are thickness, density, and fiber volume fraction. Compression strength is determined by using compression strength that follow s ASTM C-365. Impregnation and core construction quality is evaluated by visual and stereo microscope technique. Sandwich composite 3D woven fabric successfully made with good impregnation quality at weigh ratio of fiber : resin 1 : 1, 1 ; 1,1, and 1 : 1,5 with average thickness of 5,49 mm. The increase of resin results in increase of density and core compressive strength of composite sandwich woven 3D fabric. The increase of core compressive strength is caused by forming of polyester network in the column of the composite core.